2021
DOI: 10.1111/jfd.13348
|View full text |Cite
|
Sign up to set email alerts
|

Estimating cage‐level mortality distributions following different delousing treatments of Atlantic salmon (salmo salar) in Norway

Abstract: This retrospective descriptive study estimates cage‐level mortality distributions after six immediate delousing methods: thermal, mechanical, hydrogen peroxide, medicinal, freshwater and combination of medicinal treatments. We investigated mortality patterns associated with 4 644 delousing treatment of 1 837 cohorts of farmed Atlantic salmon (Salmo salar) stocked in sea along the Norwegian coast between 2014 and 2017. The mortality is expressed as mortality rates. We found distributions of delta mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Looking at the final model of ‘harvest mortality’, the number of salmon lice treatments drives the mortality and none of the significant fixed effects in the early mortality model remained significant at this stage. Treatments have been reported from several other studies to be the main cause of mortality in the Norwegian salmon farming during the last years (Bang Jensen, Qviller, et al., 2020; Overton et al., 2019; Sommerset et al., 2021) as well as a recent study showing increased mortality especially from non‐medical treatments when investigating lice treatments in detail (Sviland Walde et al., 2021). Our study supports these findings of high mortality associated with lice treatments, also by identifying ‘handling’ as the most prevalent group of mortality causes in terms of number of dead fish.…”
Section: Discussionmentioning
confidence: 94%
“…Looking at the final model of ‘harvest mortality’, the number of salmon lice treatments drives the mortality and none of the significant fixed effects in the early mortality model remained significant at this stage. Treatments have been reported from several other studies to be the main cause of mortality in the Norwegian salmon farming during the last years (Bang Jensen, Qviller, et al., 2020; Overton et al., 2019; Sommerset et al., 2021) as well as a recent study showing increased mortality especially from non‐medical treatments when investigating lice treatments in detail (Sviland Walde et al., 2021). Our study supports these findings of high mortality associated with lice treatments, also by identifying ‘handling’ as the most prevalent group of mortality causes in terms of number of dead fish.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, however, the disease has also become more common in larger sea‐farmed fish, often manifesting within a couple of weeks following non‐medicinal delousing. Such procedures, introduced in the face of increasing development of salmon‐louse resistance to chemotherapeutants, may often cause acute mortality, skin damage and poor fish welfare (Folkedal et al, 2021; Nilsson et al, 2019; Overton et al, 2019; Sviland Walde et al, 2021), and are undoubtedly extremely stressful to the subjected fish. In this study, we found eDNA from sea water equally suitable for Y. ruckeri detection by PCR as compared to freshwater, with unambiguous detection of the bacterium by both developed assays as far as 100 m downstream of a salmon sea‐cage experiencing an active Y. ruckeri CC1 infection (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…There are no published studies on fish welfare and mortality, but losses of scale, gill bleeding, wounds and salmon mortality have been recorded (Gismervik et al, 2017;Holan et al, 2017;Hjeltnes et al, 2019;Westgård, 2020). A recent study has assessed the mortality of various delousing methods and concluded that thermal and mechanical delousing have the highest overall median mortality (Walde et al, 2021).…”
Section: Flushers and Hydrolicermentioning
confidence: 99%